The Activation Conditions of the Transmission Protection Instrument: Flawed by Design? - Ivo J. M. Arnold (Intereconomics, 2023)
In 2022, the European Central Bank (ECB) introduced the Transmission ProtectionInstrument (TPI) to counter the risk of financial fragmentation following the normalisation ofmonetary policy. The ECB has specified conditions under which the TPI can be activated.This paper examines these conditions and concludes that the activation conditions cannotbe applied in an objective and transparent manner. This provides the ECB room for policydiscretion and makes the ECB susceptible to pressure from member countries. A possibleinterpretation is that the activation conditions serve as a fig leaf to cover ECB policies thatmay go beyond its mandate.
Keywords: E32; E43; E58; F45; 330; central bank; monetary policy; EU states; Zentralbank; Geldpolitik; EU-Staaten